2023
DOI: 10.14797/mdcvj.1177
|View full text |Cite
|
Sign up to set email alerts
|

Houston Methodist Ruptured Abdominal Aortic Aneurysm Guidelines

Abstract: Ruptured abdominal aortic aneurysm (RAAA) is an acute aortic condition that requires emergent intervention and appropriate continuity of care to optimize patient outcomes. We describe the standardized RAAA protocol at the Houston Methodist Hospital Acute Aortic Treatment Center, developed to navigate critical patient transfer periods safely and efficiently, make crucial decisions about surgical intervention, and clearly communicate these plans with other care team providers. Our workflow is organized into five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Nevertheless, the fundamental guiding principle of these treatment policies is the protocol-based treatment mentioned above. Until now, the introduction of HORs and the establishment of medical networks have resulted in notable improvements at each institution [ 21 ]. The well-organized protocol-based therapy has dramatically improved treatment outcomes since recent studies have reported a 30-day mortality of 14.3–23.2% [ 12 , 13 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the fundamental guiding principle of these treatment policies is the protocol-based treatment mentioned above. Until now, the introduction of HORs and the establishment of medical networks have resulted in notable improvements at each institution [ 21 ]. The well-organized protocol-based therapy has dramatically improved treatment outcomes since recent studies have reported a 30-day mortality of 14.3–23.2% [ 12 , 13 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%